PENGEMBANGAN LKPD BERBASIS PENDEKATAN SAINTIFIK SISWA KELAS VIII SMPN 12 MERANGIN - Aldo Wahyu Seprianto; Sugeng Riyadi; Ade Susanti (Hira Institute, 2026)
One of the reasons that can affect learning outcomes is the limited teaching materials. Teaching materials are tools that contain systematic materials, in this study the development of LKPD teaching materials based on a scientific approach was carried out. The purpose of this study was to produce LKPD based on a Scientific Approach that is valid, practical and effective. This type of research is research and development. The development model used in this study is 4-D which consists of the Define, Design, Development, and Disseminate stages. LKPD was validated by 5 expert validators. Validity is seen from the results of the validation sheet, practicality is seen from the results of the student response questionnaire sheet and interviews with students and teachers, while effectiveness is seen from learning outcomes and student learning activities. The results showed that the average score of the validation results by mathematics experts obtained an average score of 4.66 with a very valid category, the validation results by Indonesian language obtained an average of 4.86 with a very valid category, the validation results by media experts obtained an average of 4.83 with a very valid category, and the validation results by mathematics teachers obtained an average of 4.72. The overall validation results of the Scientific Approach-based Student Worksheet (LKPD) obtained an average score of 4.42, categorized as very valid. For product practicality, a percentage of 83.76% was obtained, categorized as practical. For product effectiveness, in terms of student learning outcomes, the percentage of completion was 80.76%, categorized as effective. Meanwhile, for student learning activities, the percentage was 70.84%, categorized as very active. Based on the results of research and development, it shows that the Scientific Approach-based Student Worksheet developed is very valid, practical, and effective